Identification of Peste des Petits Ruminants Transmission Hotspots in the Karamoja Subregion of Uganda for Targeting of Eradication Interventions - Nkamwesiga, Joseph; Coffin-Schmitt, Jeanne; Ochwo, Sylvester; Mwiine, Frank Norbert; Palopoli, Annabella; Ndekezi, Christian; Isingoma, Emmanuel; Nantima, Noelina; Nsamba, Peninah; Adiba, Rogers; Hendrickx, Saskia; Mariner, Jeffrey C. (Frontiers in Veterinary Science, 2019)
This paper describes an assessment of the patterns of peste des petits ruminants virus circulation in the Karamoja subregion of Uganda conducted to identify the communities that maintain the virus and inform the development of a targeted vaccination strategy. Participatory epidemiological methods were used to develop an operational hypothesis for the patterns of PPR in Karamoja that was subsequently validated through outbreak investigation and genomics. The participatory epidemiological assessment included risk mapping with livestock owners, community animal health workers and veterinarians and indicated there were two critical foci of virus transmission on the Uganda-Kenya border. One was located in two adjacent subcounties of Kotido and Kaabong Districts in northern Karamoja and the other in Loroo subcounty of Amudat District in southern Karamoja. Participants reported that these were locations where outbreaks were usually first observed in Karamoja and subsequently spread to other areas. Following the participatory assessment, surveillance activities were implemented across the Karamoja subregion in 2018. Three outbreak were detected, investigated and sampled. Two outbreaks were located in the northern and one on the southern focus of transmission. No Outbreaks were diagnosed in Karamoja outside of these foci during 2018. Genomics indicated different clusters of viruses were associated with the northern and southern foci that were more closely related to other East African isolates than to each other. This indicates these are two separate systems of virus circulation which should be explicitly addressed in eradication as separate cross-border systems that require integrated cross-border interventions.